Environmental life cycle assessment of biodiesel production from waste cooking oil: A systematic review. (June 2022) - Hosseinzadeh-Bandbafha, Homa; Nizami, Abdul-Sattar; Kalogirou, Soteris A.; Gupta, Vijai Kumar; Park, Young-Kwon; Fallahi, Alireza; Sulaiman, Alawi; Ranjbari, Meisam; Rahnama, Hassan; Aghbashlo, Mortaza; Peng, Wanxi; Tabatabaei, Meisam
Abstract: Waste cooking oil (WCO) disposal in landfills or discharge into sewer systems could cause severe environmental challenges. Therefore, extensive efforts are made to develop strategies for its effective management, aligned with circular bioeconomy and zero-discharge principles and the United Nations' Sustainable Development Goals. Among existing strategies, converting WCO into biodiesel is promising; however, biodiesel production from this waste stream could induce many direct and indirect environmental impacts, which should be scrutinized using advanced sustainability assessment tools. Life cycle assessment (LCA) is a powerful tool that can be applied to assess the environmental sustainability of WCO biodiesel production in comparison with diesel and first-generation biodiesel production. Accordingly, the present review aims to scrutinize the existing literature on the LCA analysis of WCO biodiesel production to shed light on the state-of-the-art of the application of this methodology in this domain, identify research gaps, and introduce future research opportunities. Although environmental assessment of biodiesel production by LCA is well-established, several limitations and concerns still exist. Overall, system boundaries have generally been clearly defined in the published literature; however, some studies have ignored waste management; for example, disposal of soap and other solid residues has usually been removed from the analysis. Furthermore, the "zero-burden assumption" applied to WCO (as biodiesel feedstock) in the published literature might not be a valid hypothesis since this waste stream could be a raw material for some other applications. At the inventory level, the inadequacy of the data, particularly information associated with the production of novel catalysts (including enzymes) and materials used for product purification, is also a problematic issue for the current and under development technologies used in WCO biodiesel production. Therefore, future studies should focus on decreasing the existing uncertainties mentioned throughout the present work. Moreover, efforts should be put into assessing the environmental impacts of WCO biodiesel production systems by employing innovative techniques, e.g., hydrodynamic cavitation reactors, integrating other renewable energy resources, and using green catalysts in the production and combustion stages of WCO biodiesel. Graphical abstract: Image 1 Highlights: Challenges of conventional treatment of waste cooking oil (WCO) are discussed. Life cycle assessment (LCA) of WCO biodiesel production is reviewed. Applying LCA analysis to evaluate biodiesel environmentally is still challenging. Zero-burden assumption for WCO might be a source of uncertainty in LCA studies. Environmental impacts of waste-based biodiesel need to be studied by novel methods.